Volunteering for development: what does best practice look like?. Issue 7 (2nd October 2020) - Thompson, Stephen; Sparrow, Karen; Hall, Jonathan; Chevis, Nicola
ABSTRACT: Volunteering for development is a long-standing form of development assistance. Vision Aid Overseas is an international NGO that works to enable people living in poverty to access affordable spectacles and eye care. Volunteering has been at the core of its interventions since its formation in 1985. In 2019 the organisation undertook a comprehensive review of its approach. A literature review and stakeholder consultation on volunteering for development were undertaken. A number of best practice recommendations were made, which were accepted by the Board of Trustees and have been used to inform a new volunteering strategy for the organisation.